THE LANGUAGE POLICY OF KAZAKHSTAN AND TURKEY AS A FACTOR OF TURKIC RELATIONS REINFORCEMENT - Turalin, Y.; Yermekbayev, A.; Kaliyeva, A. (Journal of Oriental Studies, 2023)
The Republic of Kazakhstan and the Republic of Turkey are two countries with deep historical, linguistic and cultural ties. Both belong to the category of Turkic-speaking peoples, which makes them especially close in many ways. These ties have ancient roots and have strengthened and developed over time. Turkish President Recep Tayyip Erdogan announced an initiative to create a single alphabet for Turkic countries. The Turkish President noted that member countries of the Organization of Turkic States will continue efforts to strengthen cooperation in the field of higher education in order to improve the level of human relations based on language, culture and history. “Of course, language is very important to strengthen our unity. A single alphabet is also an important component; the support of presidents is important here. Our Council of Higher Education has made special recommendations to the secretariat of the organization, and I am confident that our organization will consider this,” Recep Tayyip Erdogan said at the 10th meeting of the Organization of Turkic States in Astana in his speech at the summit (Erdogan: Language and common alphabet are important for the unity of Turkish states). These words from the head of Turkey show the importance of linguistic and cultural ties between the two countries, and this becomes the main topic of our article. In this article we study the influence of language policy on stimulating Turkic-speaking relations between Kazakhstan and Turkey, based on the historical situation and current efforts. prospects for further cooperation. Key words: organization of Turkic states, language policy, education, Turkic-speaking relations, Kazakhstan, Turkey, cooperation.